DE LA REPUBLIQUE DEMOCRATIQUE DU CONGO VOULUE INDEPENDANTE A LA REPUBLIQUE DEMOCRATIQUE DU CONGO QUI COMMEMORE SES FETES D’INDEPENDANCE - MSAMBYA, Joseph Apolo (Studia Universitatis Babes-Bolyai Studia Europaea, 2024)
From the Democratic Republic of Congo Seeking Independence to the Democratic Republic of Congo which Commemorates Its Independence Celebrations. On June 30, 1960, the independence of the Belgian Congo, once personal possession for 23 years of the Belgian King Leopold II, was proclaimed as the “Republic of the Congo”. Emery-Patrice Lumumba (1925-1961) played a capital role in this emancipation which resulted in the consecration of Joseph Kasavubu as first President of the Republic of Congo and himself, Emery Patrice Lumumba, as Prime Minister. Congo has proclaimed its independence, but the new country remains plagued by violence and infighting. Belgian troops and peacekeepers from the United Nations intervene in the territory as a standoff begins between Kasavubu and Lumumba. On September 14, 1960, Colonel Joseph Désiré Mobutu led a first coup d’état which was followed by the arrest and assassination of Lumumba. The following years would be punctuated by rebellions and fighting interspersed with ceasefires in protest against the dictatorship established by the Mobutu regime after its second coup d’état, five years later, during a new political crisis. After thirty-two years of unchallenged reign, Mobutu was ousted from power by Mzee Laurent Désiré Kabila in May 1997 and since then, it has been difficult to speak of the real independence of the country, which became the Democratic Republic of Congo.